ABUSE OF THE AUTHORITY OF VILLAGE CONSULTANCY BOARDS IN THE VILLAGE GOVERNMENT SYSTEM WORKSHOP PERBAUNGAN, SERDANG DIFFERENT REGENCY - Syahrul Bakti Harahap; Dawn Indra (SEAN Institute, 2023)
Abstract BPD is a democratic institution in the administration of villageadministration which functions to accommodate and channel community aspirations to plan and establish policies implementing village government and development. This research was conducted using normative juridical research methods. he data collection method used by the author is literature/ documentation study, namely data processing is carried out by systematizing written legal materials using a statutory and case approach. The results of this study indicate that the Village Consultative Body (BPD) has a role as a village-level legislature in accommodating, sorting, and channeling community aspirations to the Village Government as input for Village development. However, in carrying out its obligations as a Village Consultative Body (BPD), a Village Consultative Body (BPD) can be dismissed at any time for committing an offense outside of its authority, as happened to members of the Village Consultative Council (BPD) Village Workshop